Limites de perceptibilidade e aceitabilidade das alterações de cor causadas pela redução na espessura do compósito correspondente à dentina - Santos, Sheila Mara Morais (2018)
This study aimed to determine the reduction threshold on thickness of dentin shade composite necessary to result in perceptible and acceptable color changes on simulated restorations. Three composite systems (Charisma Diamond, IPS Empress Direct, and Filtek Z350 XT) were evaluated using cylinder-shaped specimens built-up with dentin and enamel shades. Opacity of the composites was assessed using 1.0 mm thick specimens over black and white backgrounds. A baseline color was established for each system by combining 1.0 mm thick enamel shade with 3.0 mm of dentin shade cylinders over a dark background (n = 9). Then, the color changes (∆E00) caused by sequential 0.1 mm reductions on dentin shade cylinders were calculated. Opacity changes on dentin shade cylinders and combined enamel-dentin pair cylinders were also assessed after each thickness reduction. Polynomial regression was performed with averages of ∆E00 as function of thickness of dentin shade cylinders; and acceptability (∆E = 1.77) and perceptibility (∆E = 0.81) thresholds were calculated. Linear regressions were also performed for ∆E00 as function of opacity of dentin shade cylinders and combined enameldentin pair of cylinders. Except for Charisma, enamel shades presented lowest opacity than dentin one. Perceptible and acceptable color changes were observed for dentin shade cylinders thinner that 2.0-2.4 mm and 1.1-1.4 mm, respectively, were used. No difference among the composite systems were observed. In conclusion, reductions of dentin shade composite lower than 0.6-mm and 1.6-mm did not result in perceptible and clinically relevant changes, respectively, on ultimate color of simulated restorations.